Desirable training of endoscopic submucosal dissection: further spread worldwide - Tsuji, Yosuke (AME Publishing Company, 2014)
Endoscopic submucosal dissection (ESD) is an excellent treatment because of its high curative resection rate and low local recurrence rate. However, its technical difficulty prevents from its permeation worldwide. For further permeation of ESD, the establishment of an appropriate training system is essential. In Japan, trainee endoscopists who have had prerequisites for ESD, that is to say, basic knowledge and skills, start ESD in accordance with a stepwise training system under close supervision by experts. The trainers select an appropriate lesion in human for each step of developments in ESD techniques. In Western countries there are few ESD experts at present, so an ex vivo animal model training must play a major role in the training system. It is desirable that these training systems should be constructed by some authorized organizations such as Japan Gastroenterological Endoscopy Society (JGES).